Detection of common bile duct dilatation on magnetic resonance cholangiopancreatography by deep learning - Ulubaba, Hilal Er; Ciftci, Rukiye; Atik, Ipek; Karakul, Osman Furkan (TURKISH SOC RADIOLOGY, 2025)
PURPOSE This study aims to detect common bile duct (CBD) dilatation using deep learning methods from artificial intelligence algorithms. METHODS To create a convolutional neural network (CNN) model, 77 magnetic resonance cholangiopancreatography (MRCP) images without CBD dilatation and 70 MRCP images with CBD dilatation were used. The system was developed using coronal maximum intensity projection reformatted 3D-MRCP images. The ResNet50, DenseNet121, and visual geometry group models were selected for training, and detailed training was performed on each model. RESULTS In the study, the DenseNet121 model showed the best performance, with a 97% accuracy rate. The ResNet50 model ranked second, with a 96% accuracy rate. CONCLUSION CBD dilatation was detected with high performance using the DenseNet CNN model. Once validated in multicenter studies with larger datasets, this method may help in diagnosis and treatment decision-making. CLINICAL SIGNIFICANCE Deep learning algorithms can aid clinicians and radiologists in the diagnostic process once technical, ethical, and financial limitations are addressed. Fast and accurate diagnosis is crucial for accelerating treatment, reducing complications, and shortening hospital stays.
Keywords: Artificial intelligence; bile duct dilatation; choledocholithiasis; convolutional neural network; magnetic resonance cholangiopancreatography; Radiology, Nuclear Medicine & Medical Imaging